Parallel and Gradual Genome Erosion in the Blattabacterium Endosymbionts of Mastotermes darwiniensis and Cryptocercus Wood Roaches - Kinjo, Yukihiro; Bourguignon, Thomas; Tong, Kwei Jun; Kuwahara, Hirokazu; Lim, Sang Jin; Yoon, Kwang Bae; Shigenobu, Shuji; Park, Yung Chul; Nalepa, Christine A; Hongoh, Yuichi; Ohkuma, Moriya; Lo, Nathan; et al. (Genome biology and evolution, 2018)
Almost all examined cockroaches harbor an obligate intracellular endosymbiont, Blattabacterium cuenoti. On the basis of genome content, Blattabacterium has been inferred to recycle nitrogen wastes and provide amino acids and cofactors for its hosts. Most Blattabacterium strains sequenced to date harbor a genome of ∼630 kbp, with the exception of the termite Mastotermes darwiniensis (∼590 kbp) and Cryptocercus punctulatus (∼614 kbp), a representative of the sister group of termites. Such genome reduction may have led to the ultimate loss of Blattabacterium in all termites other than Mastotermes. In this study, we sequenced 11 new Blattabacterium genomes from three species of Cryptocercus in order to shed light on the genomic evolution of Blattabacterium in termites and Cryptocercus. All genomes of Cryptocercus-derived Blattabacterium genomes were reduced (∼614 kbp), except for that associated with Cryptocercus kyebangensis, which comprised 637 kbp. Phylogenetic analysis of these genomes and their content indicates that Blattabacterium experienced parallel genome reduction in Mastotermes and Cryptocercus, possibly due to similar selective forces. We found evidence of ongoing genome reduction in Blattabacterium from three lineages of the C. punctulatus species complex, which independently lost one cysteine biosynthetic gene. We also sequenced the genome of the Blattabacterium associated with Salganea taiwanensis, a subsocial xylophagous cockroach that does not vertically transmit gut symbionts via proctodeal trophallaxis. This genome was 632 kbp, typical of that of nonsubsocial cockroaches. Overall, our results show that genome reduction occurred on multiple occasions in Blattabacterium, and is still ongoing, possibly because of new associations with gut symbionts in some lineages.
Keywords: Isoptera; symbióza; dřevo; Phylogeny; švábi; Genome, Bacterial; Wood; Flavobacteriaceae; genom bakteriální; Symbiosis; Animals; zvířata; fylogeneze; Cockroaches